A highly selective and sensitive 3-hydroxyflavone-based colorimetric and fluorescent probe for hydrogen sulfide with a large Stokes shift. Issue 24 (16th June 2016) - Hou, Peng; Li, Hongmei; Chen, Song
Abstract: A 3-hydroxyflavone-based colorimetric and fluorescence probe for hydrogen sulfide (H2 S) has been developed with high sensitivity and excellent selectivity. This probe was designed based on the mechanism that H2 S selectively cleaved the NBD (7-nitro-2, 1, 3-benzoxadiazole) ether moiety in this probe and therefore release the fluorophore, 3-hydroxyflavone. The addition of H2 S to the solution of probe1 resulted in a green fluorescence and an obvious color change from colorless to pink, indicating that this probe can serve as a colorimetric and fluorescent dual probe for H2 S. Furthermore, this probe displays a rapid response and reaches to a plateau within 5 min. It also exhibits a 146 nm Stokes shift and a low detection limit (20 nM, based on S/N=3) in detecting H2 S. Importantly, practical utility of this probe for the selective detection of H2 S in living cells has been successfully demonstrated. Graphical abstract: A novel colorimetric and fluorescence probe with a 146 nm Stokes shift was developed, which displayed a fast response time, exhibits high sensitivity and good selectivity for the detection of H2S in living A 431 cells.